PENINGKATAN KUALITAS EFLUEN SISTEM LUMPUR AKTIF LIMBAH CAIR INDUSTRI TAHU DENGAN VARIASI BERAT ARANG AKTIF TERHADAP VOLUME EFLUEN MENGGUNAKAN ARANG AKTIF KAYU ULIN (Eusideroxylon zwageri) - Handayani Handayani; Danang Biyatmoko; Abdullah Abdullah; Jamzuri Hadie (Universitas Lambung Mangkurat, 2016)
The purpose of this study was to (1) analyze the effect of the activation of iron wood charcoal towards improving the quality of activated charcoal based on moisture content, ash content and adsorption I2, (2) analyze the effect of weight variation activated iron wood charcoal in the activated sludge effluent to temperature parameter, TSS, pH, BOD5, COD and Ammonia, as well as getting the weight ratio of optimum active iron wood charcoal toward activated sludge effluent. The research design used a completely randomized design. The variation of weight variation of active charcoal from 0, 1, 2, 3, 4, 5 and 6 g with 3 (three) repetitions. This Research was done at the laboratory of Badan Lingkungan Hidup Banjarbaru. The conclusion of this study was that the effect of the activation of ironwood charcoal towards improvement of the quality of activated charcoal were moisture content, ash content and adsorption I2 obtained before activation was 3,02%; 2,41% and 609 mg/g, while moisture content, ash contents and adsorption I2 after being activated were 2,88%; 2,02 % and 685 mg/g. The moisture content and ash contents had reached the quality standard of SNI 06–3730-1995, but the adsorption I2 not yet. The eEffect of weight variation activated charcoal ironwood in the effluent sludge to the temperature, TSS, pH, BOD5, COD and ammonia parameter based on F-test results were highly significant (p<0,01). The parameter of temperature and pH increased as the weight of activated charcoal ironwood increased. The parameter of TSS, BOD5, COD and ammonia decreased as the weight of activated ironwood charcoal. The Parameter that did not reach the quality standard were COD and Ammonia. Optimum weight activated charcoal ironwood active against effluent activated sludge of 6 g. Optimum weight activated ironwood charcoal obtained temperature, TSS, pH, BOD5, COD and ammonia. The values of each were 27,7 0C; 35,7 mg/L; 9,01; 44,2 mg/L; 108 mg/L and 15,2 mg/L.